2017
DOI: 10.1016/j.juro.2017.02.1948
|View full text |Cite
|
Sign up to set email alerts
|

Mp62-17 Listening to Music During Shock Wave Lithotripsy Decreases Anxiety, Pain and Dissatisfaction: A Randomized Controlled Study

Abstract: included abnormally elevated renal parameters, signs of a concomitant infectious process (fever, leukocytosis, or a positive urine dipstick), pain poorly responding to analgesia, radiolucent stones, or stones smaller than 4-mm or larger than 15-mm in size. 72 patients had been randomly assigned to undergo ESWL directly without pre-stenting (Group A), while 52 patients were assigned for pre-stenting (Group B), with their data and outcomes prospectively collected. Mean patient BMI in both groups was 26.1 and 26.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Music was transmitted by smartphone, using the Spotify ® application for your selection. Previous studies show that the use of music preferably by patients favors better therapeutic effects in reducing the painful phenomenon (Cakmak et al, 2017;Chen, Seth, Rao, & Huang, 2012;Kühlmann et al, 2018;Lee, 2016;Li et al, 2019;Lunde, Vuus, Garza-Vilarreal, & Vase, 2019;Quigley et al, 2019;Song et al, 2018).…”
Section: Intervention Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Music was transmitted by smartphone, using the Spotify ® application for your selection. Previous studies show that the use of music preferably by patients favors better therapeutic effects in reducing the painful phenomenon (Cakmak et al, 2017;Chen, Seth, Rao, & Huang, 2012;Kühlmann et al, 2018;Lee, 2016;Li et al, 2019;Lunde, Vuus, Garza-Vilarreal, & Vase, 2019;Quigley et al, 2019;Song et al, 2018).…”
Section: Intervention Protocolmentioning
confidence: 99%
“…In this context, procedural pain is highlighted by its high prevalence and repercussions, being the result of tissue and/or nervous injury resulting from health procedures (Czarnecki et al, 2011). Despite its relevance, procedural pain has been underestimated in the care environment, since it is considered inherent to the procedure without considering its deleterious effects (Cakmak et al, 2017;Lee, 2016;Song et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…1). Finally, 11 articles were included in this systematic review and meta-analysis (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Details of the included studies are presented in Table I.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Outcomes. A total of nine studies reported pain outcomes on the VAS scale (22)(23)(24)26,(28)(29)(30)(31)(32). Pooled analysis indicated a statistically significant difference in pain outcomes in favor of media distraction (MD: -1.18; 95% CI: -2.35, -0.01; I 2 =96.8%; Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation